INFLUENCE OF ACOUSTIC FREQUENCY ON BEAN GERMINATION AND GROWTH PROCESS - ALISA MOȘNEAGA; VALENTIN NEDEFF; PETRU LOZOVANU (Journal of Engineering Studies and Research)
In this work, research findings on processing bean seeds with sound waves in the range 0-9 kHz are presented. The process of germination has been examined for seeds soaked in heat treated water and plain water. In the initial stage, the conditions necessary to stimulate plant growth were created. The paper describes the experimental setup and the sound wave seed treatment procedure. The characteristics of the seed germination process were determined and compared with those of the control sample germination.